The translation projects of Maria Eleonora von Sporck and María Francisca de Montijo. Women’s translation practices in the 18th century - Gabriela Eichlová (Cornova)
This paper responds to recent research on linguistic and more broadly cultural translation in the field of cultural exchange and transfer studies. The study will focus on two translation projects undertaken by women in the eighteenth century for whom translation was not a profession, namely Maria Elenora von Sporck (1687–1717) and María Francisca de Montijo (1754–1808). Two types of translation activities will be examined: 1) translations from French into German in the Czech Germanophone environment and 2) translation from French into Castilian in a Spanish-speaking environment. The two francophone noblewomen from Catholic backgrounds translated books with spiritual and moral themes, but somewhat surprisingly they were authors suspected of religious heterodoxy. This fact, among other things, invites us to take a closer look at the extra-textual factors, in addition to textual ones, that influenced the emergence of these translations. Focusing on women translators of heterodox texts the study thus aims to extend the research on the early modern translation. It also seeks to contribute to contemporary discussions on the reconceptualization of agency, especially with an emphasis on the concept of collaborative authorship, and, finally, to contribute to the assessment of the applicability of translatological concepts to early modern translations.